Traumatic Abdominal Wall Hernias: Classification, Diagnosis and Management - Mincu, Andrei; Mușat, Florentina; Ion, Daniel; Bolocan, Alexandra; Păduraru, Dan Nicolae; Andronic, Octavian (Scripta Medica, 2020)
Traumatic abdominal wall hernias (TAWHs) are uncommon health conditions that involve a disruption of the muscular layers after a blunt abdominal injury. A consensus in the management of TAWHs has not been established, owing to the scarce number of reported cases. These hernias can occur under a broad array of clinical presentations, from stable and asymptomatic patients to emergency situations with associated intra-abdominal injuries. The aetiology of TAWHs is diverse and can occur at all ages, however it is more likely to be reported in children and elderly patients. Clinical findings must be correlated with a CT scan, which will confirm the diagnosis. Early diagnosis and treatment were found to be associated with a lower risk of complications and mesh use during the surgical repair is an efficient mean of reducing recurrences after the surgical repair. However, the timing of repair and surgical solution still depends on the patient’s condition.
Keywords: Traumatic abdominal wall hernia; Traumatic abdominal wall defect; Blunt abdominal injury; Blunt abdominal trauma; Intra-abdominal injuries